ICD-10 WHO Search With RAKE Algorithm - Wijayakusuma, I Gusti Ngurah Lanang; Gautama, I Putu Winada (Jurnal Matematika; Vol 13 No 2 (2023)DO - 10.24843/JMAT.2023.v13.i02.p163, 2023)
In most cases, clinicians do not use the ICD-10 standard established by the WHO for diagnosing diseases. These issues may result in outcomes that are undesirable from the standpoints of patient safety and the law. The WHO ICD-10 standard collection of diagnoses that can’t be effectively searched using MySQL’s native search mechanism. Therefore, in order to automatically produce several keywords for each ICD-10 code, academics are interested in analyzing the natural language analysis of WHO ICD-10 data. When diagnosing illnesses, it is envisaged that the availability of numerous types of keywords can lead to more fruitful search results. Natural language analysis, a technique for removing stop words from sentences and simultaneously assessing the semantics of the language from which the keywords will be extracted, makes it possible to do this. Keywords : Natural Language Analysis ; ICD-10 ; Stop Words ; Semantic s.